PRIORITIES IN CONCEPT OF CARDIOVASCULAR RISK FACTORS IN IRRADIATED PATIENTS AT DISTANT PERIOD AFTER CHERNOBYL NUCLEAR DISASTER BASED ON PROSPECTIVE COHORT DATA - R. G. Oganov; V. S. Sherashov; N. V. Sherashova; M. V. Sherashova; S. K. Kukushkin; O. G. Rudakova; E. A. Zhavoronkova (Столичная издательская компания, 2016)
Aim. To study pathogenetic mechanisms and cardiovascular risk factors prospective cohort study in liquidators of consequences of Chernobyl Nuclear Disaster 13-20 years after an accident.Material and methods. 409 irradiated patients and 224 control patients comparable on the age and gender were involved into two-stage cohort prospective study with 4,5years period of observation. Database included results of standard questionnaires, social and demographic description, education, family status, smoking and alcohol habits, anthropometry, fasting lipids and glucose, blood pressure, ECG, arrhythmias on ECG monitoring, heart rhythm variability, Echocardiography, thyroid ultrasound image, spirometry, transesophageal electrophysiological study of heart conduction system, exercise tests, functional class of ischemic heart disease, stage of arterial hypertension, fatal/nonfatal end-points, as well as neurologist, endocrinologist and cardiologist conclusions. Totally 267 variables were included in the analysis.Results. Spectrum of active cardiovascular risk factors in cohort of irradiated patients was entirely different from this in control patients. Determinative value for irradiated patients was related with night hypersympathetic activity, ANDS syndrome (Autonomic Nervous Dysfunction on hyperSympathetic type) and less related with decreased airway conductance in small bronchial tubes.Conclusion. Comparative prospective cohort study in liquidators of consequences of Chernobyl Nuclear Disaster 13-20 years after an accident revealed highly significant new and permanently acting cardiovascular risk factors. These data let to work out appropriate approaches to therapy and prevention of cardiovascular diseases.